How advancement in bone science should inform the examination and treatment of femoral shaft bone stress injuries in running athletes - Hegedus, E. J.; Mulligan, E. P.; Beer, B. A.; Gisselmann, A. S.; Wooten, L. C.; Stern, B. D. (Sports Medicine, 2023)
Stress fractures likely have a 1-2% incidence in athletes in general. In runners, a more vulnerable population, incidence rates likely range between 3.2 and 21% with female runners having greater susceptibility. The incidence of femoral shaft stress fractures is less well known. New basic and translational science research may impact the way clinicians diagnose and treat femoral stress fractures. By using a fictitious case study, this paper applies bone science to suggest new approaches to evaluating and treating femoral shaft stress fractures in the running population.